Pengaruh penerapan model problem based learning dalam pembelajaran daring terhadap hasil belajar siswa - Supartin Supartin; Hidjrawaty Tantu; Mursalin Mursalin; Asri Arbie; Ritin Uloli; Dewa Gede Eka Setiawan (Educatio, 2022)
Learning amid the COVID-19 pandemic underwent significant changes, the implementation of learning which was initially carried out face-to-face at school, became learning from home/belajar dari rumah (BDR). On the other hand, the strategy should make students think at a higher level. Based on observations, it was found that students were still very lacking in understanding physics learning and learning methods that seemed monotonous and boring. So to overcome these problems, the application of a problem based learning model is carried out. This study aims to determine the effect of applying the problem-based learning model in online learning on student learning outcomes in heat material. This type of research is included in the type of quantitative research. The research method used is experimental. Subjects in the study were students of SMP Negeri 6 Gorontalo City in class VII. It consisted of three (3) classes, namely the experimental class, replication 1, and replication 2. The instrument used in this study was a written test (essay) consisting of pre-test and post-test. test. The process of collecting data through written tests in the form of pretest and posttest to see the consistency of the influence of student learning outcomes. The data analysis technique used is the normalized gain test (n-gain), the normality test of the hypothesis test data. The results show that learning by applying the Problem Based Learning model can affect student learning outcomes. This is shown through the hypothesis testing criteria where for the experimental class tcount 7.304 is greater than ttable 2,035, for replication class 1 tcount 8,266 the value is more dominant than ttable 2,037, and for replication class 2 tcount 9,658 is greater than ttable 2,037 so it can be said that the test the hypothesis tcount is more dominant than ttable, this can be interpreted that the Problem Based Learning model is quite influential in student learning outcomes.